Epidemiology and Mycological Analysis of Superficial Mycosis in a Northern Indian Tertiary Care Hospital - Nishima Sharma; Jasmina Javaid; Pankaj Kaul (International Journal of Fungi, 2024)
Background: A fungal infection that affects the outer layer of the skin and its connective tissue, including hair and nails, is called superficial mycosis. These infections are typically caused by fungi, which thrive on keratin, the proteinthat makes up the nails, hair, and skin. A common disease that can affect people of any age, gender, or race is superficial mycosis. Usually, it appears as a streaky red rash that can be uncomfortable or painful. In some cases, the infection may lead to hair loss, nail discoloration, or thickening of the affected area. Aim And Objectives: The aim of this research is to conduct a observational study to investigate the clinico-mycological characterization of superficial mycosis among patients in a tertiary care hospital in North India. Material And Methods: This study was conducted at National Hospital Section 6, Mohali, Punjab, over a period of four months, from February to May, using prospective laboratory controls from patients who had superficial mycoses, and samples forty in all gave forty. The specimens underwent macro- and microscopical examinations, and growth was tracked for a maximum of four weeks. The present study was planned to characterize the different dermatophytes, budding yeast like fungi in various types of superficial mycosis. Examine skin scrapings, hair plucking and nails with direct bacterial examination (KOH mount) and culture on Sabouraud dextrose agar Result: Trichophyton species occurred in 7 cases (17.5%) of 40 samples taken from individuals with suspected superficial mycosis, making it the most frequent clinical group in the Sample, 14 (35%) regular showed positive results in KOH mounts, while 22 (55%.), positive in culture Results were shown. Females 16 (72%) were the most commonly affected than males 6(18%). Conclusions: The research conducted in this research has revealed that superficial mycosis is commonly caused by dermatophytes, common types include tinea corporis (ringworm), tinea pedis (athlete's foot), tinea capitis (scalp ringworm), and Trychophyton species. Any clinical diagnosis must be backed up with a lab diagnosis. To conclusively identifying the etiological agent, culture is an essential supplement to direct microscopic inspection.
Keywords: Fungal infections; Superficial mycosis; dermatophytosis; tenia pedis; trichophyton